AWZ1066S, a highly specific anti-Wolbachia drug candidate for a short-course treatment of filariasis - Hong,WD; Benayoud,F; Nixon,GL; Ford,L; Johnston,KL; Clare,RH; Cassidy,A; Cook,DAN; Siu,A; Shiotani,M; Webborn,PJH; Kavanagh,S; et al. (Proceedings of the National Academy of Sciences of the United States of America, 2019)
Onchocerciasis and lymphatic filariasis are two neglected tropical diseases that together affect ∼157 million people and inflict severe disability. Both diseases are caused by parasitic filarial nematodes with elimination efforts constrained by the lack of a safe drug that can kill the adult filaria (macrofilaricide). Previous proof-of-concept human trials have demonstrated that depleting >90% of the essential nematode endosymbiont bacterium, Wolbachia, using antibiotics, can lead to permanent sterilization of adult female parasites and a safe macrofilaricidal outcome. AWZ1066S is a highly specific anti-Wolbachia candidate selected through a lead optimization program focused on balancing efficacy, safety and drug metabolism/pharmacokinetic (DMPK) features of a thienopyrimidine/quinazoline scaffold derived from phenotypic screening. AWZ1066S shows superior efficacy to existing anti-Wolbachia therapies in validated preclinical models of infection and has DMPK characteristics that are compatible with a short therapeutic regimen of 7 days or less. This candidate molecule is well-positioned for onward development and has the potential to make a significant impact on communities affected by filariasis.